2014
DOI: 10.1016/j.eplepsyres.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes during posterior epilepsies: An EEG-fNIRS study

Abstract: Posterior epilepsies are relatively rare, mainly suspected clinically by the presence of visual auras.Functional near-infrared spectroscopy (fNIRS) is an emerging non-invasive imaging technique that has the potential to monitor hemodynamic changes during epileptic activity. Combined with electroencephalography (EEG), 9 patients with posterior epilepsies were recorded using EEG-fNIRS with large sampling (19 EEG electrodes and over 100 fNIRS channels). Spikes and seizures were carefully marked on EEG traces, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Unlike ictal SPECT, which can provide only a single perfusion brain image of cerebral blood flow during a seizure, combined EEG‐fNIRS offers a continuous method of studying regional hemodynamic and oxygenation changes that occur before, during, and after seizures. Our method of recording seizures using EEG‐fNIRS was described in detail previously …”
Section: Methodsmentioning
confidence: 99%
“…Unlike ictal SPECT, which can provide only a single perfusion brain image of cerebral blood flow during a seizure, combined EEG‐fNIRS offers a continuous method of studying regional hemodynamic and oxygenation changes that occur before, during, and after seizures. Our method of recording seizures using EEG‐fNIRS was described in detail previously …”
Section: Methodsmentioning
confidence: 99%
“…In particular, our group has been working towards implementing long-term EEG-fNIRS in the epilepsy unit and neurological intensive care unit with the development of wireless and wearable multichannel wearable system dedicated for simultaneous EEG-fNIRS acquisitions at the bedside (Lareau et al, 2011;Le Lan et al, 2013) and showed that the technique has definite potential to detect, localize and assess the impact of focal seizures Pouliot et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Regarding rehabilitation, a BCI system has the capacity to distinguish improvement from non-improvement as a result of therapy and brain stimulation. Detection of seizures (Nguyen et al, 2012, 2013), epilepsy (Peng et al, 2014; Pouliot et al, 2014; Visani et al, 2015), and estimation of improvement in motor functions after stroke (Das et al, 2016) are such examples pursuing hBCI for patients. The current BCI system, however, lacks the potential to provide detailed functions.…”
Section: Applicationsmentioning
confidence: 99%